Estética Noigandres: vanguardismo e antimimese no projeto concretista (1952-1964) - Souza, Leandro Candido de (2014)
This work analyzes the concretist proposal presented by the activities of the Noigandres group formed by poets Augusto de Campos (1931-), Haroldo de Campos (1929-2003) and Decio Pignatari (1927-2012). Our thesis consists in the integration of the three poets through their different practices into a modeling artistic-cultural project whose strategy worked well tuned to the postmodern doxa of the commodification of modernism, the formalization of avantgarde and the utilitarian refunctionalisation of art. The abandonment of style and adoption of the text, the relationship established with the art institution, the theoretical-historical revisionism, the epistemological debate and the jump into the mass media confirm that a large distance has established between the concretists of Sao Paulo and the so-called high modernism at the turn of the century and its criticism by the historical avant-garde movements. Finally, we attempted to re-establish the analytical intersection from different sources - which consisted this doctrine - to draw from them notes on what was the role played by the three poet-makers in cultural disputes experienced in the course of the modernization process of Brazilian capitalism